Answer:
i think the answer is C
Step-by-step explanation:
<u><em>Note: As you may have unintentionally missed to add the value choices. But, I would make sure to explain the concept so that you may improve your understanding in terms of solving these type of questions.</em></u>
Answer:
Any value other than the values
will not be a solution of
.
Step-by-step explanation:
Considering the equation
![8x^3\:-\:1\:=\:0](https://tex.z-dn.net/?f=8x%5E3%5C%3A-%5C%3A1%5C%3A%3D%5C%3A0)
Steps to solve the equation
![8x^3-1=0](https://tex.z-dn.net/?f=8x%5E3-1%3D0)
![\mathrm{Add\:}1\mathrm{\:to\:both\:sides}](https://tex.z-dn.net/?f=%5Cmathrm%7BAdd%5C%3A%7D1%5Cmathrm%7B%5C%3Ato%5C%3Aboth%5C%3Asides%7D)
![8x^3-1+1=0+1](https://tex.z-dn.net/?f=8x%5E3-1%2B1%3D0%2B1)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![x^3=\frac{1}{8}](https://tex.z-dn.net/?f=x%5E3%3D%5Cfrac%7B1%7D%7B8%7D)
![\mathrm{Divide\:both\:sides\:by\:}8](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D8)
![\frac{8x^3}{8}=\frac{1}{8}](https://tex.z-dn.net/?f=%5Cfrac%7B8x%5E3%7D%7B8%7D%3D%5Cfrac%7B1%7D%7B8%7D)
![\mathrm{Simplify}](https://tex.z-dn.net/?f=%5Cmathrm%7BSimplify%7D)
![x^3=\frac{1}{8}](https://tex.z-dn.net/?f=x%5E3%3D%5Cfrac%7B1%7D%7B8%7D)
As
![\mathrm{For\:}x^3=f\left(a\right)\mathrm{\:the\:solutions\:are\:}x=\sqrt[3]{f\left(a\right)},\:\sqrt[3]{f\left(a\right)}\frac{-1-\sqrt{3}i}{2},\:\sqrt[3]{f\left(a\right)}\frac{-1+\sqrt{3}i}{2}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7Dx%5E3%3Df%5Cleft%28a%5Cright%29%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Dx%3D%5Csqrt%5B3%5D%7Bf%5Cleft%28a%5Cright%29%7D%2C%5C%3A%5Csqrt%5B3%5D%7Bf%5Cleft%28a%5Cright%29%7D%5Cfrac%7B-1-%5Csqrt%7B3%7Di%7D%7B2%7D%2C%5C%3A%5Csqrt%5B3%5D%7Bf%5Cleft%28a%5Cright%29%7D%5Cfrac%7B-1%2B%5Csqrt%7B3%7Di%7D%7B2%7D)
![x=\sqrt[3]{\frac{1}{8}},\:x=\sqrt[3]{\frac{1}{8}}\frac{-1+\sqrt{3}i}{2},\:x=\sqrt[3]{\frac{1}{8}}\frac{-1-\sqrt{3}i}{2}](https://tex.z-dn.net/?f=x%3D%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B8%7D%7D%2C%5C%3Ax%3D%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B8%7D%7D%5Cfrac%7B-1%2B%5Csqrt%7B3%7Di%7D%7B2%7D%2C%5C%3Ax%3D%5Csqrt%5B3%5D%7B%5Cfrac%7B1%7D%7B8%7D%7D%5Cfrac%7B-1-%5Csqrt%7B3%7Di%7D%7B2%7D)
So,
![x=\frac{1}{2},\:x=-\frac{1}{4}+i\frac{\sqrt{3}}{4},\:x=-\frac{1}{4}-i\frac{\sqrt{3}}{4}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B1%7D%7B2%7D%2C%5C%3Ax%3D-%5Cfrac%7B1%7D%7B4%7D%2Bi%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B4%7D%2C%5C%3Ax%3D-%5Cfrac%7B1%7D%7B4%7D-i%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B4%7D)
Therefore,
Any value other than the values
will not be a solution of
.
Keywords: solution, value
Learn more about equation solution from brainly.com/question/1679491
#learnwithBrainly
Answer:
9* 3 ^ (x-2)
Step-by-step explanation:
g(x) = 3^x
We know a^ (b) * a^(c) = a^ (b+c)
9* 3 ^ (x+2) = 3^2 * 3 ^(x+2) = 3^(2+x+2) = 3^x+4 not equal to 3^x
3*(9^(x+2)) = 3*3^2(x+2) = 3^1 * 3^(2x+4) =3^(2x+4+1) = 3^(2x+5) not equal
9* 3 ^ (x-2) = 3^2 * 3 ^(x-2) = 3^(2+x-2) = 3^x equal to 3^x
3*(9^(x-2)) = 3*3^2(x-2) = 3^1 * 3^(2x-4) =3^(2x-4+1) = 3^(2x-3) not equal
Answer:
whats your insta?
Step-by-step explanation:
X 3/5 =2x+15=2x=15-2x=13
answer 13